Floristic Diversity and Distribution Pattern of Plant Communities along Altitudinal Gradient in Sangla Valley, Northwest Himalaya - Pankaj Sharma; J. C. Rana; Usha Devi; S. S. Randhawa; Rajesh Kumar (The Scientific World Journal)
Himalayas are globally important biodiversity hotspots and are facing rapid loss in floristic diversity and changing pattern of vegetation due to various biotic and abiotic factors. This has necessitated the qualitative and quantitative assessment of vegetation here. The present study was conducted in Sangla Valley of northwest Himalaya aiming to assess the structure of vegetation and its trend in the valley along the altitudinal gradient. In the forest and alpine zones of the valley, 15 communities were recorded. Study revealed 320 species belonging to 199 genera and 75 families. Asteraceae, Rosaceae, Apiaceae, and Ranunculaceae were dominant. Among genera, Artemisia followed by Polygonum, Saussurea, Berberis, and Thalictrum were dominant. Tree and shrub’s density ranged from 205 to 600 and from 105 to 1030 individual per hectare, respectively, whereas herbs ranged from 22.08 to 78.95 individual/m2. Nearly 182 species were native to the Himalaya. Maximum altitudinal distribution of few selected climate sensitive species was found to be highest in northeast and north aspects. This study gives an insight into the floristic diversity and community structure of the fragile Sangla Valley which was hitherto not available.